2003
DOI: 10.2754/avb200372010055
|View full text |Cite
|
Sign up to set email alerts
|

Epidemology of Intraspecies Bite Wounds in Dogs in the Czech Republic

Abstract: The epidemiology of bite wounds in dogs that resulted from intraspecies conflicts and were treated at the Small Animal Clinic, Department of Surgery and Orthopedics, University of Veterinary and Pharmaceutical Sciences, Brno was evaluated from 246 records in 1989-90 and 337 records in 1998-99. The number of bite incidents fluctuated during the year. The majority of incidents occurred in summer months, i.e. in the second (n = 149) and third (n = 193) trimester of the year. In comparison, only 119 and 122 bite v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
4
11
0
Order By: Relevance
“…In agreement with this notion is our report (Baranyiová et al 2003) that seniors aged 12-to-15 years became victims of interdog aggression in only 1% of incidents. Ability of old dogs to perceive, process and remember information about their environment obviously diminished.…”
Section: Discussionsupporting
confidence: 84%
“…In agreement with this notion is our report (Baranyiová et al 2003) that seniors aged 12-to-15 years became victims of interdog aggression in only 1% of incidents. Ability of old dogs to perceive, process and remember information about their environment obviously diminished.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, known dogs bit when the children approached or tried to take the dog's toy or caused them pain by accident. Similar to Hart and Miller (1985) and Rieck (1997) we found that male dogs bit more frequently than female dogs; analysis of dog-dog bites revealed about 70% biting males and the most frequent injuries in these conflicts were those of the head region (Baranyiová et al 2003) unlike injuries inflicted on children (Náhlík 2005).…”
Section: Discussionsupporting
confidence: 88%
“…Dogs' bite injuries were localized in 80.7% patients in a single area of the face, while two or more areas were involved in 19.7%. These figures correspond to findings published by Baranyiova et al [17] As for the isolated soft tissue injuries, without bites impact on bones, we can assume that the injured person or some other person may have prevented the dog to continue it's attack and provoke more severe facial injuries.…”
Section: Animal Bite Injuriessupporting
confidence: 90%
“…It may be suggested that men are generally more interested in having a dog or that men develop rough relationship with dogs. Whatever the case is, it results in an increased risk for men to be attacked and injured by dogs [6,13,17]. Results of the present study are revealing that children and young individuals were more frequently bitten by dogs than older individuals, and there are several reasons that explain these findings.…”
Section: Animal Bite Injuriesmentioning
confidence: 67%